2009
DOI: 10.13031/2013.25424
|View full text |Cite
|
Sign up to set email alerts
|

Nozzle and Carrier Application Effects on Control of Soybean Leaf Spot Diseases

Abstract: Increased soybean foliar disease potential has heightened grower interest in fungicide application techniques. Application field trials comparing application rate [187 vs. 112 L/ha (20 vs. 12 gal/acre)], nozzle style (twin-orifice; single-orifice) and spray quality (fine vs. medium and coarse spray quality), and application technique (with and without air-assist) along with an unsprayed check were done at two locations over two years. Fungicide deposition (coverage and droplet size) and disease severity in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 8 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…The addition of the soybean oil methyl-ester adjuvant to the spray may reduce the volumetric median diameter of the spray droplets relative (Sasaki et al, 2015). The reduction of the diameter of the droplets in turn provides greater penetration of the spray droplets in the canopy of the soybean crop (Hanna, Robertson, Carlton, & Wolf, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The addition of the soybean oil methyl-ester adjuvant to the spray may reduce the volumetric median diameter of the spray droplets relative (Sasaki et al, 2015). The reduction of the diameter of the droplets in turn provides greater penetration of the spray droplets in the canopy of the soybean crop (Hanna, Robertson, Carlton, & Wolf, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…WSP is a specific type of paper coated with bromoethyl blue, a dye that appears yellow, but turns blue when hydrated by water-containing droplets impacting the coated paper collectors (Turner and Huntington 1970). The use of WSP for characterization of sprays in the field has been on-going for 45 years (Turner and Huntington 1970) and is the most widely used collector type for canopy penetration studies (Knoche 1994;Derksen et al 2008;Wolf and Daggupati 2009;Hanna et al 2009;Derksen et al 2014).…”
Section: Spray Application Of the Artificial Collectorsmentioning
confidence: 99%
“…Canopy penetration is the ability of sprayed droplets to move through a canopy to provide adequate control of pests. Previous studies have examined canopy penetration in several cropping systems to identify which application techniques and technologies maximize canopy penetration (Knoche 1994;Zhu et al 2004;Derksen et al 2008;Hanna et al 2009;Derksen et al 2014;Creech 2015;Ferguson et al 2016). These studies observed that coarser sprays improved canopy penetration within several crop canopy types.…”
Section: Spray Application Of the Artificial Collectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the pesticides that are used to protect crops of economic interest, fungicides and insecticides have greater difficulty reaching their targets than herbicides because insects and fungi are often present in regions of the plant where the spray droplets cannot readily penetrate the barriers created by the top leaves. The penetration of droplets through the leaf canopy is more difficult as the leaf area indices increase HANNA et al, 2009). …”
Section: Introductionmentioning
confidence: 99%